Manajemen Penggunaan AI dalam Rekrutmen dan Karier: Studi Kasus Perusahaan - Bahdin Nur Tanjung; Jumadiah Wardati; Gita Nainggolan (Jurnal Pariwisata Tawangmangu, 2025)
This study, titled AI Use Management in Recruitment and Career: A Case Study of a Company, aims to analyze how artificial intelligence (AI) is implemented and managed in recruitment, performance appraisal, and career management, along with examining its effects on employees and the ethical challenges that arise. Using a qualitative case study approach in a company that has adopted AI systems, the research collected data through in-depth interviews, document studies, field observations, and quantitative data analysis (e.g., screening time, conversion rate, and employee satisfaction). The findings indicate that AI improves recruitment efficiency by automating candidate screening and interview scheduling, and it enables more objective performance evaluations based on real-time data analysis. Furthermore, AI supports career development and internal mobility through data-driven recommendations aligned with employees’ performance and preferences. Nevertheless, the study also highlights risks of algorithmic bias and limited transparency (“black box”), implying the need for regular audits, human oversight, and clear internal policies to ensure that AI is used fairly, responsibly, and ethically.